Synthesis and Interaction Investigation of a Non-ionic Surfactant in Aqueous Medium at Different Temperatures - Partap, Ram; Swaroop, Neelam (Asian Journal of Chemistry, 2016)
The surface tension data have been utilized for evaluation of surface and thermodynamic parameters. Isooctylphenoxypolyethoxy ethanol (TX-100) with/without aqueous Na2SO4 has been reported at 288.15, 293.15 and 298.15 K. Thermodyanamic parameters indicate that processes are endothermic in nature but negative values of DG0mic and positive DS0mic favours the process of micellization.